Hypocholesterolemic effect of diets, supplemented with either whole or phenol-free bambangan peel powder on an animal model. - Abdulrahman Hassan, Fouad; Ismail, Amin; Abdul Hamid, Azizah; Azlan, Azrina; Al-Sheraji, Sadeq Hasan (2011)
Objective: To estimate the potential hypolipidemic effects of antioxidant dietary fiber (AOOF) by comparing oftwo diets in dietary-induced hypercholesterolemic rats. Methods: The experiment was performed on normal and 3 hypercholesterolemic groups of growing male Sprague Dawley rats. During 6 weeks they were fed different diets: negative control (NC) group fed with normal diet, the positive control (PC) group fed diet incorporated with 2% cholesterol and 5% cellulose as standard DF, and two experimental groups (EG I), (EG2) fed the same diet incorporated with 70g of whole or phenol-free dry bambangan peel/kg (providing 5% OF), respectively. Lipid profile, malondialdehyde, activity of the antioxidant enzymes GPx and SOD were measured in plasma in addition to the determination of fecal bile acids excretion. Results: The results showed a statistically significant increase (P < 0.05) in plasma TC andLOL-C only in PC and EG2. The EGI showed significant reduction (P < 0.05) of lipid profile except of l-lOL-C, returning plasma TC and LOL levels to the normal range found in NC. An equal increase of lipid peroxides (LP) was registered in the EG2 and PC as compared to that of EGI. No apparent effects on the activity of plasma antioxidant enzymes were observed.Increased bile acids excretion in was also observed in both EG I, EG2. These effects might be attributed to the presence of the natural polyphenols and high of content in dried bambangan peel. Conclusion: Finding ofthe present study has indicated that the hypolepedomic effect of this fruit peel is associated with the antioxidanmt dietary fiber (AOOF). However, the antioxidant effect is associated mainly with peel phenols.